2022
DOI: 10.1016/j.ijscr.2021.106732
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted ventral sacral Tarlov cystectomy; A case report

Abstract: Introduction and importance Although asymptomatic Tarlov cysts (TCs) are reported in up to 13% of the population, symptomatic TCs are rare (less than 1%), making the management of the symptomatic cysts controversial. The most common location of symptomatic TCs is sacral nerve roots where they can cause pelvic, perineal chronic discomfort and pain, and lower extremity sensory and motor changes. Ventral (intrapelvic retroperitoneal) sacral TCs are extremely rare with no management recommendations. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Sacral TC are generally benign, and incidentally found [2] . Previous studies have suggested that TCs can be found in up to 13% of the general population, the vast majority in asymptomatic patients [ [9] , [10] , [11] ]. Approximately 1% of the population with TC become symptomatic [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sacral TC are generally benign, and incidentally found [2] . Previous studies have suggested that TCs can be found in up to 13% of the general population, the vast majority in asymptomatic patients [ [9] , [10] , [11] ]. Approximately 1% of the population with TC become symptomatic [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%